2012
DOI: 10.1080/10652469.2011.627510
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal matrix polynomials satisfying differential equations with recurrence coefficients having non-scalar limits

Abstract: Abstract. We introduce a family of weight matrices W of the form T (t)T * (t), T (t) = e A t e Dt 2 , where A is certain nilpotent matrix and D is a diagonal matrix with negative real entries. The weight matrices W have arbitrary size N × N and depend on N parameters. The orthogonal polynomials with respect to this family of weight matrices satisfy a second order differential equation with differential coefficients that are matrix polynomials F 2 , F 1 and F 0 (independent of n) of degrees not bigger than 2, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…, where it was shown that the polynomials that satisfy a relation of the form xPkfalse(xfalse)=AkPk+1false(xfalse)+BkPkfalse(xfalse)+Ak1Pk1false(xfalse) for k=0,1,, are orthogonal with respect to a positive definite matrix of measures; ie, a matrix version of Favard's theorem. Then, in the 1990s and the 2000s, it was found that MOPs satisfy in some cases similar properties as the classical orthogonal polynomials, ie, the scalar‐type Rodrigues' formula and a second‐order differential equation . It has been proven that operators of the form D = 2F2false(tfalse) + 1F1false(tfalse) + 0F0 have eigenfunctions of different infinite families of MOPs.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…, where it was shown that the polynomials that satisfy a relation of the form xPkfalse(xfalse)=AkPk+1false(xfalse)+BkPkfalse(xfalse)+Ak1Pk1false(xfalse) for k=0,1,, are orthogonal with respect to a positive definite matrix of measures; ie, a matrix version of Favard's theorem. Then, in the 1990s and the 2000s, it was found that MOPs satisfy in some cases similar properties as the classical orthogonal polynomials, ie, the scalar‐type Rodrigues' formula and a second‐order differential equation . It has been proven that operators of the form D = 2F2false(tfalse) + 1F1false(tfalse) + 0F0 have eigenfunctions of different infinite families of MOPs.…”
Section: Introductionmentioning
confidence: 98%
“…A new family of MOPs satisfying second‐order differential equations whose coefficients do not behave asymptotically as the identity matrix was found in Ref. ; see also Ref. .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of such polynomials goes back at least to [19] and we refer to the survey paper [8] for a detailed discussion of the available literature and for many more references. Some recent developments and applications of matrix orthogonal polynomials can be found in [4,6,9,17] among many others.…”
Section: Introductionmentioning
confidence: 99%
“…This is a matrix version of Favard's theorem for scalar orthogonal polynomials. Then, in the 1990's and the 2000's some authors found that matrix orthogonal polynomials (MOP) satisfy in certain cases some properties that satisfy scalar valued orthogonal polynomials; for example, Laguerre, Hermite and Jacobi polynomials, i.e., the scalar-type Rodrigues' formula [44,45,34] and a second order differential equation [46,47,24]. Later on, it has been proven [48] that operators of the form D=∂ 2 F 2 (t)+∂ 1 F 1 (t)+∂ 0 F 0 have as eigenfunctions different infinite families of MOP's.…”
mentioning
confidence: 99%